Analisis Kinerja Kelompok Kerja IV Pemberdayaan Kesejahteraan Keluarga Dalam Penanganan Balita Stunting Di Kelurahan Semanan Jakarta Barat Tahun 2023 - Muchtar, Mochamad Hanifan; Chaerunisyah, Ana (Jurnal Ilmu Administrasi Publik, 2024)
Cases of toddlers at risk of stunting always exist in Semanan Village. Access to health information is recognized as a major factor in community empowerment efforts. Health problems in the Semanan District, West Jakarta, are the task of Working Group IV for Family Welfare Empowerment as a government empowerment organization to become a pioneer in empowering families and communities. This research aims to analyze the role and performance of Working Group IV Empowerment of Family Welfare in Semanan Village and determine the Supporters and Barriers in handling stunting in Semanan Village. The research method used is a qualitative research method with a descriptive research type with data collection techniques through direct interviews with informants with indicators of performance dimensions by Robbins, and data analysis techniques are inductive, and the results of qualitative research emphasize meaning rather than generalizations. From the research results, it was found that Working Group IV Empowerment of Family Welfare in Semanan Village has a role in planning and implementing stunting handling activities and has structured performance in coordination with related parties and is also scheduled in the implementation of activities. There are obstacles such as the insight of posyandu officers regarding stunting and from residents who are still reluctant to open up and are lazy to come regularly to monitor the growth and development of their toddlers and also support activities for handling stunting such as the existence of CSR.